2021
DOI: 10.1101/2021.09.27.21264121
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CovRNN—A recurrent neural network model for predicting outcomes of COVID-19 patients: model development and validation using EHR data

Abstract: Background: Predicting outcomes of COVID-19 patients at an early stage is critical for optimized clinical care and resource management, especially during a pandemic. Although multiple machine learning models have been proposed to address this issue, based on the need for extensive data pre-processing and feature engineering, these models have not been validated or implemented outside of the original study site. Methods: In this study, we propose CovRNN, recurrent neural network (RNN)-based models to predict C… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
(22 reference statements)
0
8
0
Order By: Relevance
“…EMR data, which typically represents a patient's history as a sequence of visits with multiple events per visit, is well-suited for such sequence models as RNNs [64,65]. Recent studies indicated that simple-gated RNN models, such as Gated Recurrent Units (GRUs) and Long Short-Term Memory (LSTMs), when finely tuned using Bayesian Optimization, often deliver competitive outcomes [33]. Due to the limited sample size, we did not use Transformerbased models, which require a large amount of data for training.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…EMR data, which typically represents a patient's history as a sequence of visits with multiple events per visit, is well-suited for such sequence models as RNNs [64,65]. Recent studies indicated that simple-gated RNN models, such as Gated Recurrent Units (GRUs) and Long Short-Term Memory (LSTMs), when finely tuned using Bayesian Optimization, often deliver competitive outcomes [33]. Due to the limited sample size, we did not use Transformerbased models, which require a large amount of data for training.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, we built a deep-learning-based model, DeepBiomarker, through modification of an established deep-learning framework, Pytorch_EHR [33,34]. In DeepBiomarker, we used diagnosis, medication use, and lab tests as the input, implemented data augmentation technologies to improve the model performance, and also integrated a perturbation-based approach [35] for risk factor identification.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the implementation codes, we conducted data pre-processing on a Python-based pipeline, which resulted in patients’ comprehensive clinical profiling in a unified time sequence. We utilized the packages in scikit-learn 1.0.1 for RF and LR, an anaconda-supported package for LGBM, and an EHR-tailored predictive pipeline pytorch_ehr (32, 33) for GRU and RETAIN.…”
Section: Methodsmentioning
confidence: 99%
“…We adopted the Pytorch_EHR framework established by Zhi Group where Deep learning models based multiple recurrent neural networks 21 were used to analyze and predict clinical outcomes 22 . In conjunction with their algorithm and our previous DeepBiomarker model, we further modi ed the framework as DeepBiomarker2 by (a) integrating individual lab tests, SDoH parameters and medications along with the diagnosis groups as the input, so that we can assess the important clinical and nonclinical factors associated with ASUD risk; and (b) re ning contribution analysis 23 module by re ning the relative contribution analysis for the identi cation of key factors (see below for more details).…”
Section: Deepbiomarker2mentioning
confidence: 99%